Zimbabwe : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Zimbabwe. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights that Zimbabwe's economy is facing difficulties. A severe drought and slow reform momentum have led to high expenditure levels since late 2015 despite subdued revenues. With limited access to foreign inflows, the ensuing fiscal imbalances have become unsustainable, and are being financed by rising domestic borrowing. Growth in 2017 is expected to be supported by a strong performance in agriculture mainly owing to exceptional rains. However, economic activity in the medium term is projected to remain subdued, pending adjustment and reform that tackle the structural challenges and enable the economy to restore fiscal and external sustainability and achieve its growth potential.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet